Impact of interferon-γ release assay on the latent tuberculosis cascade of care: a population-based study. Issue 3 (23rd March 2017) - Roth, David Z.; Ronald, Lisa A.; Ling, Daphne; Chiang, Leslie Y.; Cook, Victoria J.; Morshed, Muhammad G.; Johnston, James C.
Latent tuberculosis infection (LTBI) screening and treatment can have a significant impact on TB incidence if a high proportion of at-risk people successfully complete an adequate course of LTBI therapy [1–5]. Patient loss and dropouts occur at multiple points along the LTBI screening and treatment process, ultimately resulting in a minority of high-risk people completing LTBI therapy. To understand the public health impact of new screening and treatment strategies, we need to evaluate the impact of various interventions on the LTBI cascade of care. Sequential TST–IGRA testing may reduce LTBI therapy and improve treatment completion without increasing active TB http://ow.ly/2Kzr307W1tm